Renal Transplantation in the Setting of Prior Urinary Diversion: A Case of Poorly Differentiated Adenocarcinoma in an Ileal Conduit - R.S. Matulewicz; J.P. Fryer; X.J. Yang; R. Goyal; J.C. Hairston (Urology Case Reports, 2015)
Though rare, renal transplantation into a bowel containing urinary diversion is necessary in select clinical situations. Compared to renal transplant patients with functional native bladders, patients with urinary diversion have comparable long-term graft and patient survival rates. However, compounding the increased risk of malignancy in those on chronic immunosuppression are the inherent risks of urinary diversion. We present a case report of a high grade adenocarcinoma with neuroendocrine differentiation arising in an ileal conduit and discussion on the pathophysiology, management, and screening of this highly select population.